1999
DOI: 10.1097/00005392-199907000-00017
|View full text |Cite
|
Sign up to set email alerts
|

P53 Mutations in Bladder Tumors Inactivate the Transactivation of the P21 and Bax Genes, and Have a Predictive Value for the Clinical Outcome After Bacillus Calmette-Guerin Therapy

Abstract: The p53 mutations, using functional assay in yeast, inactivate the transcription of p21 and Bax genes, and based on these preliminary results could have a useful predictive value for BCG therapy response in bladder cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…The proportion of p53 alterations detected by FASAY in T a -T 1 tumors in the present series was similar to the proportion reported by Pfister et al, 36.5% (19 of 52) versus 34% (16 of 47), respectively (22), as was the percentage of positive FASAY in invasive TCCs [83% (5 of 6) versus 100% (4 of 4), respectively], grade 2 tumors (17% versus 18%, respectively), and grade 3 tumors (79% versus 61%, respectively). However, we also compared FASAY and p53 immunohistochemistry.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The proportion of p53 alterations detected by FASAY in T a -T 1 tumors in the present series was similar to the proportion reported by Pfister et al, 36.5% (19 of 52) versus 34% (16 of 47), respectively (22), as was the percentage of positive FASAY in invasive TCCs [83% (5 of 6) versus 100% (4 of 4), respectively], grade 2 tumors (17% versus 18%, respectively), and grade 3 tumors (79% versus 61%, respectively). However, we also compared FASAY and p53 immunohistochemistry.…”
Section: Discussionsupporting
confidence: 92%
“…To improve The critical biochemical function of p53 in carcinogenesis and tumor progression relies on alterations of the transcription of target genes controlling cell growth and apoptosis (16). Therefore, the use of a functional assay in yeast to selectively identify inactivating p53 mutations in bladder tumors, first reported by Pfister et al in 1999, seems to be a more valuable alternative to immunohistochemistry (16,21,22). In this study, the transcriptional activity of p53 was compared with p53 and p21 at the protein and gene expression levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, Pfister and coworkers prospectively reviewed 60 superficial bladder tumors and reported that a significant percentage of high-grade tumors had been shown to have the p53 mutation in contrast to low-grade tumors [49]. They found that p53 was significantly associated with a BCG-refractory phenotype.…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…It has been reported that in superficial bladder cancers, p53 mutations may inactivate the transcription of bax gene. 26 Bax is a member of the bcl-2 family and has a pro-apoptotic effect. 27 Although the phenomenon of p53 overexpression in TCC has mostly been reported to have underlying genetic mutations, 28 the authors can not conclude that the p53 positivity observed in our cases are accompanied by p53 mutation, and hence the exact role of mutant and/or wild-type p53 expression on frequency of apoptosis and bcl-2 in TCC requires more studies.…”
mentioning
confidence: 99%